Pengenalan Matematika Melalui Permainan Pada Anak Usia Dini: Analisis Bibliometrik tahun 2016-2025 - Rina Sari Lubis; Muhammad Zia Alghar; Liliana Hasibuan (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2025)
This study aims to map publication trends and intellectual structure of literature on play integration in early childhood mathematics education from 2016 to 2025. A bibliometric approach was applied to data from Scopus using VOSviewer, Biblioshiny, and Microsoft Excel. Results show progressive publication growth with significant acceleration post-2022, indicating a shift from niche to mainstream research. Early Childhood Research Quarterly and Journal of Experimental Child Psychology emerged as the most dominant sources. The most productive author was Ramani G.B. (7 documents), followed by Hu B.Y. and Li L. (6 documents each). The most prolific institutions were University of California (13 documents), University of Pittsburgh, and University of Toronto (12 documents each). The United States dominated country contributions, followed by Canada, China, and Sweden. Co-occurrence keyword analysis revealed a thematic shift toward experimental approaches linking play with cognitive constructs such as numeracy, executive function, and school readiness. These findings confirm the field's maturation while highlighting representation gaps from developing countries, providing strategic direction for developing evidence-based and inclusive play-based mathematics learning research and practice.